Rewolucja komunistyczna i dyktatura proletariatu w świetle publikacji Centralnego Porozumienia Organizacji Współdziałających w Zwalczaniu Komunizmu – zarys problemu - Sacewicz, Karol (Pamięć i Sprawiedliwość, 2017)
In the history of the Second Republic of Poland, the issue of attitude toward the activities of communist groups was one of the most important matters affecting its internal and external security. The state apparatus as well as Polish political and social organisations, guarding independence, sovereignty and the territorial integrity of Poland as well as in the name of their own particular political objectives, were undertaking cross-sectoral activities for the mitigation or elimination of the communist threat. The continuous and extremely real threat of the communist factors caused a natural reaction from the Polish state. Communism created anti-Communism. The latter was not a propaganda invention, whim or hysteria of the Polish political groups, but it was in line with the Polish national interest. One of the social agendas conducting anti-communist activities was the Central Agreement of the Organisations Co-operating in the Fight Against Communism. In its publications, it analysed the programme-related and propaganda activities of the Communists including the Communist Party in Poland, with special reference to the issue of revolution and the dictatorship of the proletariat. The aim of the publication is to present the state of knowledge possessed and used in its political and journalistic activities by the Agreement.